Blood loss and duration of surgery are independent risk factors for complications after breast reconstruction. Issue 5 (3rd September 2017) - Thorarinsson, Andri; Fröjd, Victoria; Kölby, Lars; Modin, Albert; Lewin, Richard; Elander, Anna; Mark, Hans
Abstract: Background: Complications after breast reconstructive surgery are common, and they can be caused by a wide range of factors. The aim of the present study was to identify independent perioperative risk factors for postoperative complications after breast reconstruction. Methods: A retrospective study was performed of 623 consecutive breast cancer patients who had undergone deep inferior epigastric perforator (DIEP) flap, latissimus dorsi (LD) flap, lateral thoracodorsal flap (LTDF), or tissue expander with secondary implant (EXP). Data on demography, perioperative parameters, and complications were collected. Logistic regression models adjusted to the reconstruction method and to confounding demographic factors were used for statistical analysis. Results: Increased blood loss for each 10-ml step increased the risk for overall early complications ( p = 0.017), early seroma ( p = 0.037), early resurgery ( p = 0.010), late local overall complications ( p = 0.024), and late fat necrosis ( p = 0.031). Longer duration of surgery for each 10-minute step increased the risk of overall early complications ( p = 0.019), but, in the univariate model, there was an increased risk for nine different types of complications ( p = 0.004–0.029). There was no association between the experience of the surgeon performing the procedure and the frequency of complications. Conclusions: Duration of surgery and blood loss during surgery are independent risk factors for postoperative complications, and should be minimised. Further research is needed to establish the association between the experience of the surgeon and the occurrence of complications.